Latihan Jalan Kaki untuk Meningkatkan Vitalitas Lansia - Ni Putu Wulan Purnama Sari; Maria Manungkalit; Agustina Chriswinda Bura Mare; Yohana Maria Meliani Septiasih Sat (LPMP Imperium, 2024)
This activity aimed to maintain or increase the vitality of the elderly living in nursing home so as to optimize health status in old age. The method used were health education (HE) program about walking exercise, demonstration and redemonstration of walking exercise, as well as measuring vital sign (blood pressure) of the elderly before and after walking exercise. The instruments used were knowledge questionnaire, walking exercise observation sheet, and vital sign observation sheet. Parameters measured were the level of knowledge and blood pressure. Participants were elderly people living in a private nursing home in Surabaya (n=82). The majority were elderly women (79.3%) who were in the old category, namely 75-90 years old (59.8%). Before the HE program, the majority had insufficient knowledge about walking exercise (43.9%), then this level was increased became a sufficient level in the majority after the HE program (56.1%). There were 26 elderly participated in the walking exercise redemonstration (31.7%), all of whom were hypertensive. Before walking exercise, the Mean systolic blood pressure was 142.96 mmHg and the Mean diastolic was 75.92 mmHg. After walking exercise, 100% elderly experienced a decrease in systolic blood pressure with a Mean of 122.73 mmHg and diastolic with a Mean of 68.42 mmHg. There were only 7.7% elderly who did not experience a decrease in diastolic blood pressure after walking exercise. The results of the Wilcoxon Signed Rank test showed that walking exercise had a significant effect on systolic (p=0.000) and diastolic (p=0.002) blood pressure in hypertensive elderly. Walking exercise is a very appropriate sport for the elderly.